2013
DOI: 10.1002/grl.50332
|View full text |Cite
|
Sign up to set email alerts
|

An unidentified emission in Titan's upper atmosphere

Abstract: [1] We have analyzed limb daytime observations of Titan's upper atmosphere at 3.3 m, acquired by the visual-infrared mapping spectrometer (VIMS) on Cassini. They were previously studied by García-Comas et al. (2011) to derive CH 4 densities. Here, we report an unidentified emission peaking around 3.28 m, hidden under the methane R branch. This emission is very strong, with intensity comparable to the CH 4 bands located in the same spectral region. It presents a maximum at about 950 km and extends from 600 km u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…Fullerenes have also been suggested as candidates for the negative ions [ Sittler et al , ]. An unidentified feature at 3.28 μm in mesospheric measurements from VIMS [ Dinelli et al , ] has been attributed to a collection of PAHs with an average mass of 430 Da [ López‐Puertas et al , ]. However, unambiguous identifications in this mass range will require a higher‐resolution mass spectrometer on a future mission.…”
Section: Titan's Atmospheric Structure and Compositionmentioning
confidence: 99%
“…Fullerenes have also been suggested as candidates for the negative ions [ Sittler et al , ]. An unidentified feature at 3.28 μm in mesospheric measurements from VIMS [ Dinelli et al , ] has been attributed to a collection of PAHs with an average mass of 430 Da [ López‐Puertas et al , ]. However, unambiguous identifications in this mass range will require a higher‐resolution mass spectrometer on a future mission.…”
Section: Titan's Atmospheric Structure and Compositionmentioning
confidence: 99%
“…This is what motivated the development of the Titan Haze Simulation (THS) experiment at the NASA Ames Cosmic simulation facility (Ricketts and Salama, 2008), which had been initially developed for the study of PAHs in astrophysical context (Salama, 2008 and references therein). Furthermore, recent measurements from the Cassini Visible Infrared Mapping Spectrometer (VIMS) revealed an unidentified emission at 3.28 lm (Dinelli et al, 2013) detected between 600 km and 1250 km (with a maximum at 950 km) that could be an indication of the presence of aromatic hydrocarbon molecules such as PAHs in the upper atmosphere of Titan (Lopez-Puertas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dinelli et al (2013) and López-Puertas et al (2013) have attributed a daytime emission feature observed at 3.28 μm in Cassini/VIMS limb spectra to aromatic hydrocarbons contained in the haze at altitudes of 600−1250 km (with a maximum around 950 km). The predominant absorption by heavy alkane ices at ∼60−500 km altitude in the 1−5 μm VIMS solar occultation spectra seems at odds with their results.…”
Section: Resultsmentioning
confidence: 99%